Theoretical and practical considerations regarding the illegal access to a computer system in the Romanian Criminal Law - Sadîc, Zafer (Technium Social Sciences Journal, 2021)
The article analyzes the legal framework for regulating the crime of illegal access to a computer system in the Romanian legal system, with a brief foray into the history of criminalization of unauthorized access to a computer system, continues with the indication of the normative text in force, after which it describes the structure and legal content of the crime, with specific references to recent relevant criminal jurisprudence.